Design and Performance Analysis of Compact Wearable Textile Antennas for IoT and Body-Centric Communication Applications. (24th August 2021) - Varma, Sanjit; Sharma, Somia; John, Merbin; Bharadwaj, Richa; Dhawan, Anuj; Koul, Shiban K.
Abstract : This paper presents two compact textile-based planar dipole and loop antennas for wearable communication applications operating in the 2.4 GHz industrial, scientific, and medical radio (ISM) bands. The antennas were fabricated on a 0.44 mm thin camouflaged-military print, cotton jean cloth using conductive copper threads, and sewing embroidery technique to create the radiating structure. Design and performance analyses of the antennas were carried out using simulations; further experiments were performed in anechoic chamber and indoor environment to validate the designs. The experiments were carried out in a free space scenario and on the various locations of the human subject such as the torso and limb joints. The performance of the antennas was investigated based on the reflection coefficient in normal and bent conditions corresponding to the different radii of the locations of the human limbs. The antennas perform well in free space and on-body scenarios in flat and bend conditions providing return loss below −10 dB in all cases with an acceptable resonant frequency close to 2.4 GHz due to the antenna bending and body effects. The radiation pattern measurements are also reported in this work for free space and on-body scenarios. It is observed that the presence of the human body significantly influences the antenna radiation pattern which leads to an increase in the front-to-back ratio and also makes the antenna more directive. Overall, the performance of the fabricated embroidered textile antennas was found suitable for various wearable body-centric applications in indoor environments.